Diversity of cave Phlebotomines (Diptera: Psychodidae) from a Colombian cave (2022)
ABSTRACT: Sandflies are vector species of Leishmania, among many other pathogens, with a global distribution and a variety of ecological niches. Previous samplings have found that karstic formations (i.e., caves, grottos, and folds formed by the erosion of limestone) serve as a natural habitat to sandfly species. The majority of samplings of cave sandfly diversity have occurred in Brazil and to date none have studied the species composition in a cave in the Northern Andes. We collected sandflies in the Cave “Los Guácharos”, in the state of Antioquia, Colombia. The sampling was carried out during two consecutive nights in September 2019. CDC-type light traps were installed inside the cavern and in other surrounding karst systems (caves, rock-breaks, and folds). In total, we identified 17 species of sandfly from the cave and surrounding karst systems, including a new record for Colombia (Bichromomyia olmeca), and provide the first karstic reports for four other species (Lutzomyia gomezi, Lutzomyia hartmanni, Pintomyia ovallesi, and Psychodopygus panamensis). We then used the results of our survey and published literature to test two hypotheses. First, that sandfly diversity in Neotropical caves is richest nearer to the equator, and second that there is a phylogenetic signal of karstic habitat use in sandflies. Counter to our predictions, we found no evidence that diversity follows a latitudinal gradient. Further, we find no evidence of a phylogenetic signal of karstic habitat use, instead finding that the use of caves likely evolved multiple times across several genera. Our results highlight the importance of a wide sampling to understand the natural habitat of sandflies and other disease vectors.